Sistem Informasi Pariwisata Daerah Istimewa Yogyakarta Berbasis Website Menggunakan Microsoft PowerApps - Moch Bagoes Pakarti; Tiara Fitri Wardani, Ananda (LPPM ITB AAS Indonesia, 2022)
Tourism has become one of the basic needs of society in the modern era. With the development of increasingly sophisticated technology, the need for information on tourism objects is getting higher. The Special Region of Yogyakarta is one of the provinces that has 7,854,170 visitors, both foreign and domestic, in 2021. With so many tourist objects spread across 78 districts throughout Yogyakarta, an information system is needed that can provide complete tourist object data to make it easier tourists in determining the tourist destinations to be visited. Microsoft PowerApps is Power Apps is a number of applications, services and connectors, as well as a data platform, which provides a fast development environment for building custom applications for business needs with the Windows platform which is the most popular operating system in Indonesia. With the implementation of a tourism information system, it can facilitate tourists in determining tourist trips and tourist objects to be visited and facilitate the management of existing information sources.